Genetically enhanced asynapsis of autosomal chromatin promotes transcriptional dysregulation and meiotic failure - Homolka, David (Springer-Verlag, 2011)
During meiosis, pairing of homologous chromosomes and their synapsis are essential prerequisites for normal male gametogenesis. Even limited autosomal asynapsis often leads to spermatogenic impairment, the mechanism of which is not fully understood. The present study was aimed at deliberately increasing the size of partial autosomal asynapsis and analysis of its impact on male meiosis. For this purpose, we studied the effect of t (12) haplotype encompassing four inversions on chromosome 17 on mouse autosomal translocation T(16;17)43H (abbreviated T43H). The T43H/T43H homozygotes were fully fertile in both sexes, while +/T43H heterozygous males, but not females, were sterile with meiotic arrest at late pachynema. Inclusion of the t (12) haplotype in trans to the T43H translocation resulted in enhanced asynapsis of the translocated autosome, ectopic phosphorylation of histone H2AX, persistence of RAD51 foci, and increased gene silencing around the translocation break. Increase was also on colocalization of unsynapsed chromatin with sex body. Remarkably, we found that transcriptional silencing of the unsynapsed autosomal chromatin precedes silencing of sex chromosomes. Based on the present knowledge, we conclude that interference of meiotic silencing of unsynapsed autosomes with meiotic sex chromosome inactivation is the most likely cause of asynapsis-related male sterility. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00412-011-0346-5) contains supplementary material, which is available to authorized users.